2019
DOI: 10.1038/s41598-019-41147-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Functional Human Esophageal Mucosa Explant Platform to Eosinophilic Esophagitis

Abstract: There is an increasing prevalence of esophageal diseases but intact human tissue platforms to study esophageal function, disease mechanisms, and the interactions between cell types in situ are lacking. To address this, we utilized full thickness human donor esophagi to create and validate the ex vivo function of mucosa and smooth muscle (n = 25). Explanted tissue was tested for contractile responses to carbachol and histamine. We then treated ex vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…19 , 20 Both primary esophageal fibroblasts and smooth muscle cells secrete fibronectin at baseline culture conditions and increase secretion following stimulation. 21 , 22 Fibronectin and periostin were detected immunohistochemically in visceral smooth muscle but not normal submucosa in CE, but were markedly reduced or absent in visceral smooth muscle in ES (not shown), consistent with ES smooth muscle having secreted them into the extracellular matrix in the architecturally altered areas in ES. Fibronectin was identified in the extracellular matrix of ES in addition to periostin, and esophageal fibroblasts and smooth muscle cells could have been sources.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…19 , 20 Both primary esophageal fibroblasts and smooth muscle cells secrete fibronectin at baseline culture conditions and increase secretion following stimulation. 21 , 22 Fibronectin and periostin were detected immunohistochemically in visceral smooth muscle but not normal submucosa in CE, but were markedly reduced or absent in visceral smooth muscle in ES (not shown), consistent with ES smooth muscle having secreted them into the extracellular matrix in the architecturally altered areas in ES. Fibronectin was identified in the extracellular matrix of ES in addition to periostin, and esophageal fibroblasts and smooth muscle cells could have been sources.…”
Section: Discussionmentioning
confidence: 63%
“…24 TGFb also mediates the increased secretion of fibronectin by primary esophageal fibroblasts or smooth muscle cells co-cultured with eosinophils or eosinophil products. 18,21,22 Secretion of TGFb may have increased muscle cell contractility and fibronectin secretion in the ES in this study since it was detected immunohistochemically in cells consistent with mast cells.…”
Section: Esophageal Connective Tissue Secretes Components Of the Extr...mentioning
confidence: 68%
See 2 more Smart Citations
“…Therefore, blocking this mechanism may affect the progress of gastrointestinal stromal tumor [ 24 ]. Kurten et al [ 25 ] found that the gene expression of fibronectin and smooth muscle actin was risen in eosinophilic esophagitis. The degree of ATP2A2 inhibition was determined by PLN oligomeric state, and phosphorylation of phosphatidylinositol could reduce the inhibition of ATP2A2.…”
Section: Discussionmentioning
confidence: 99%